Effects of single and multiple applications of glyphosate or aminopyralid on simple constructed plant communities. (29th August 2014) - Pfleeger, Thomas; Blakeley‐Smith, Matthew; Lee, E. Henry; King, George; Plocher, Milton; Olszyk, David
Abstract To determine effects of multiple applications of herbicides on small constructed plant communities, Prunella vulgaris L.var. lanceolata Fern, Festuca roemeri (Pavlick) Alexeev, Clarkia amoena (Lehm.) Nels., and Cynosurus echinatus L. were grown together in small field plots. Plants were treated with glyphosate at target concentrations of 0 × , 0.01 × , 0.1 × , and 0.2× a field application rate (FAR) of 1122 g ha−1 active ingredient (a.i.) for 3 yr in 1 location, and for 2 yr in a second location. Plants also were treated with aminopyralid at 0 × , 0.037 × , 0.136 × , and 0.5× FAR of 123 g ha−1 a.i. for 2 yr in 2 locations. Plants received 1, 2, or 3 applications of each herbicide each year. Species and community responses depended on herbicide concentration and number of applications. With glyphosate, plant volume (modified formula for a cone) tended to decrease for all species (especially C. echinatus), and the decreases generally became larger with more applications. Plant communities exposed to the 2 greatest concentrations initially differed from controls but then appeared to recover. With aminopyralid, C. amoena was essentially eliminated from the communities, especially at the 2 greatest FARs, whereas the other 3 species tended to have significant increases in volume, especially at the 2 smallest FARs. With aminopyralid, increasing numbers of applications produced variable results, and the plant community volume never tended to recover. Environ Toxicol Chem 2014;33:2368–2378. Published 2014 Wiley Periodicals Inc., on behalf of SETAC. This article is a US Government work and, as such, is in the public domain in the United States of America.